EFFICACY OF LINEZOLID OVER VANCOMYCIN IN TREATING METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) INFECTIONS. - NAVODHYA JINDAL; SONIA JAIN; DHRITIMAN MAITRA (International Journal of Pharma and Bio Sciences, 2015)
The purpose of this analysis was to compare the efficacy and safety of linezolid versus vancomycin in patients with nosocomial pneumonia, complicated skin & soft- tissue infections and sepsis by methicillin-resistant Staphylococcus aureus (MRSA).This study was conducted on hospitalized patients of a tertiary care hospital in Kolkata, West Bengal. Out of 191 patients, 130 received linezolid 600 mg (IV or oral) every 12 hours and 61 received vancomycin 1 g every 12 hours IV. Clinical success rates at the end of the treatment were 94.6% and 90.16% for the linezolid and vancomycin groups respectively (p=0.2564) and microbiological eradication rates were 93.07% and 88.52% respectively (p=0.2901) showing no significant difference in the efficacy of two drugs. Drug related adverse events were reported in 0.7% and 1.63% of the patients treated with linezolid and vancomycin respectively with thrombocytopenia (3.84%) reported only in patients who received linezolid. Linezolid is as effective as vancomycin however intravenous or oral linezolid was well tolerated.